Considerations in Orbital Exenteration - Sokoya, Mofiyinfolu; Cohn, Jason E.; Kohlert, Scott; Lee, Thomas; Kadakia, Sameep; Ducic, Yadranko (Seminars in Plastic Surgery, 2019)
Orbital exenteration (OE) is a radical operation associated with significant psychosocial disability and functional impairment. Indications for OE include primary tumors of the eye, oral cavity, paranasal sinuses, skin, and brain. Careful consideration regarding the likelihood of local control and cure is needed before proceeding with this operation. Multidisciplinary work-up should be performed before proceeding with surgery. The method of reconstruction after OE should be tailored to the defect and the postoperative needs of the patient. Appropriate follow-up and rehabilitation should be arranged for the patient.
Keywords: orbital exenteration; orbital invasion; globe resection